Sense of Coherence Mediates the Relationship Between Cognitive Reserve and Cognition in Middle-Aged Adults - Cattaneo, Gabriele; Solana-Sánchez, Javier; Abellaneda-Pérez, Kilian; Portellano-Ortiz, Cristina; Delgado-Gallén, Selma; Alviarez Schulze, Vanessa; Pachón-García, Catherine; Zetterberg, H.; Tormos, Jose Maria; Pascual-Leone, Alvaro; Bartrés-Faz, David (Frontiers in Psychology, 2022)
In recent years, supported by new scientific evidence, the conceptualization of cognitive reserve has been progressively enriched and now encompasses not only cognitive stimulating activities or educational level, but also lifestyle activities, such as leisure physical activity and socialization. In this context, there is increasing interest in understanding the role of psychological factors in brain health and cognitive functioning. In a previous study, we found that these factors mediated the relationship between cognitive reserve and self-reported cognitive functioning. Here we wanted to confirm an association between two important constructs included in the psychological well-being and salutogenic models, “Purpose in life” and “Sense of coherence”, cognitive reserve – as assessed using a questionnaire- and cognitive functioning – as evaluated with a comprehensive neuropsychological battery. Results from 888 middle-aged healthy participants from the Barcelona Brain Health Initiative indicate that both Sense of coherence and cognitive reserve were positively associated with verbal memory, reasoning and attention, working memory and global cognition. Moreover, the relation between cognitive reserve and cognitive functioning in the different domains is partially mediated by Sense of coherence. When we control for brain integrity, introducing into the model neurofilament light chain measures, the mediator role of Sense of coherence was confirmed for reasoning and attention and global cognition. Purpose in life, however, was not associated with cognitive functioning. These results reveal the central role of the Sense of Coherence construct, which mediates the association between classic cognitive reserve estimates and cognitive functions, potentially representing a modifiable target for interventions that aim to promote brain health.